Design and develoment of a fixed wing micro air vehicle - De La Hera Fernandez, Ignacio (2017)
Micro aerial vehicles are a relatively recent topic in the aeronautic sector and their goal is to create a flying vehicle as small and lightweight as possible with the highest possible endurance. The design of these vehicles comes with some main issues related with the aerodynamics for low Reynolds numbers and low aspect ratio wings. In this project a micro air vehicle, more specifically a fixed wing micro air vehicle, has been designed. In order to do this, thoroughly analysis of the aerodynamics, structural and propulsion systems have been done. All the systems have been analyzed one by one and taken into account when analyzing the others. The analysis has been done using theoretical calculations as well as different software, such as XFLR5. After all the calculation and software design was done, it was manufactured, ensemble together and got ready to fly. Several tests were made to check the performance in real life. The tests did not turn out the way expected as the aircraft was not able to take off. However, the reason behind the problems was a found and future development would be required in order to fix them.